Antimicrobial resistance among canine enterococci in the northeastern United States, 2007–2020 - Osman, Marwan; Altier, Craig; Cazer, Casey (Frontiers in Microbiology, 2023)
Antimicrobial resistance (AMR) is a growing and complex One Health concern worldwide, threatening the practice of human and veterinary medicine. Although dogs are a potential reservoir of multidrug-resistant bacteria, there are very few surveillance studies on AMR from the canine population in the United States. Here, we assessed the antimicrobial susceptibility patterns, identified temporal resistance and minimum inhibitory concentration trends, and described associations between resistance phenotypes among canine clinical enterococci in the northeastern United States. Through a large-scale retrospective study design, we collected species identification, minimum inhibitory concentration, and clinical data from 3,659 canine enterococci isolated at the Cornell University Animal Health Diagnostic Center between 2007 and 2020. We used the Mann-Kendall test, Sen's slope, multivariable logistic regression, and survival analysis models to detect the presence of a significant trend in resistance over the study period. Enterococcus faecalis was the most prevalent species (67.1% of isolates), followed by Enterococcus faecium (20.4%). We found high levels of AMR among enterococci to almost all the tested antimicrobials, particularly E. faecium. The lowest percentage of resistance was to vancomycin and chloramphenicol. Multidrug resistance was common (80% of E. faecium and 33% of E. faecalis) and 31 isolates were extensively drug resistant. Multidrug resistance among E. faecium increased over time, but not in E. faecalis. Resistance to penicillins, enrofloxacin, and rifampin increased during the study period, but resistance to tetracyclines is on a downward trajectory compared to AMR data from the last decade. Emerging vancomycin-resistant E. faecalis (0.3%) and E. faecium (0.8%) infections in the canine population are of great concern to both human and animal health. One E. faecium isolate with acquired vancomycin resistance was identified in 2017 and four vancomycin-resistant enterococci isolates were identified in 2020. There is a crucial need to make rational prescribing decisions on the prudent use of antimicrobials and improve the quality of care for patients, especially when empirical antimicrobial treatment for enterococcal infection is common.